Formyl Peptide Receptor Activation Elicits Endothelial Cell Contraction and Vascular Leakage - Wenceslau, Camilla F.; McCarthy, Cameron G.; Webb, R. Clinton (Frontiers in Immunology, 2016)
The major pathophysiological characteristic of systemic inflammatory response syndrome (SIRS) and sepsis is the loss of control of vascular tone and endothelial barrier dysfunction. These changes are attributed to pro-inflammatory mediators. It has been proposed that in patients and rats without infection, cell components from damaged tissue are the primary instigators of vascular damage. Mitochondria share several characteristics with bacteria, and when fragments of mitochondria are released into the circulation after injury, they are recognized by the innate immune system. N-Formyl peptides are common molecular signatures of bacteria and mitochondria and are known to play a role in the initiation of inflammation by activating the formyl peptide receptor (FPR). We have demonstrated that infusion of mitochondrial N-formyl peptides (F-MIT) leads to sepsis-like symptoms, including vascular leakage. We have also observed that F-MIT, via FPR activation, elicits changes in cytoskeleton-regulating proteins in endothelial cells. Therefore, we hypothesize that these FPR-mediated changes in cytoskeleton can cause endothelial cell contraction and, consequently vascular leakage. Here, we propose that endothelial FPR is a key contributor to impaired barrier function in SIRS and sepsis patients following trauma.